Kebebasan Politik Menurut Hannah Arendt dan Relevansinya Bagi Masyarakat Indonesia - Ranubaya, Fransesco; Nikodemus; Endi, Yohanes (Talenta Publisher, 2023)
The study focuses on freedom and politics, which are often contrasted, as if politics and freedom are contradictory. There is an assumption that there is no freedom in politics or that people are free to do anything with politics. This assumption has developed so that the two can never be united. In the political situation, a political theorist named Hannah Arendt felt an anxiety. The purpose of writing this scientific paper is to explore the idea of political freedom according to Hannah Arendt and find its relationship in Indonesian society. The method used in this writing is the literature method with a literature approach. The research results of this study discuss work that is not related to daily activities (labor) but work (work) for a common goal. Meanwhile, in relation to Indonesian politics, work ethic is an attitude that leads to the best results, high competitiveness, optimism and looking for productive and innovative ways to sustain an independent Indonesia. Regarding freedom, Arendt takes the Athenian polis as a model of communicative and open speech space which is the same as politics